External Audit in Public Administration and its Impacts - Buček, Jan (2022)
The integrating research objective of this doctoral dissertation is to find out the efficacy of the functioning (audit activity) of the Czech SAO with regard to the government-imposed corrective measures, the amount of media reactions, notifications to the tax authorities, criminal notifications, the rate at which the issued recommendations were met, the number of legislative changes, and the formulation of possible recommendations with regard to the established international practice and/or the identified problematic processes within the activities of the Czech SAO. In this respect, the author – among other things – wants to find out whether audits with a greater impact in the form of corrective measures imposed by the government were in fact more expensive than audits without such corrective measures, or whether since the publication of „Control in public administration“ by the Czech and Slovak authors the SAO has shifted its focus on audits from the formal component, associated mainly with accounting errors, to the content component. With regard to the volume of audited expenditures within the mandate of the Supreme Audit Institutions, the work also aims to identify the variables that increase with this sum, respectively, those that positively relate to it. Part of this research represents also a comparison with established audit practices in the selected EU countries. By fulfilling the set goal, this work should contribute to the existing expert literature that deals with the issue of Supreme Audit Institutions, external audits within the public sector, and the associated impacts. As part of the published research results, attention was also drawn to the identified shortcomings or problem areas related to the current set-up of external audit activities in the public sector.